2019
DOI: 10.1136/bmjgh-2018-001167
|View full text |Cite
|
Sign up to set email alerts
|

Social return on investment of emergency obstetric care training in Kenya

Abstract: IntroductionEmergency obstetric care (EmOC) training is considered a key strategy for reducing maternal and perinatal morbidity and mortality. Although generally considered effective, there is minimal evidence on the broader social impact and/or value-for-money (VfM). This study assessed the social impact and VfM of EmOC training in Kenya using social return on investment (SROI) methodology.MethodsMixed-methods approach was used, including interviews (n=21), focus group discussions (n=18) incorporating a value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…A review of 116 1‐ to 5‐day simulation‐based studies from around the world on emergency obstetric care training for hospital staff at all levels, demonstrated that similar to our course, short competency‐based training can result in a change in clinical practice and significant improvement in skills and knowledge 17 . Similarly, in Kenya, a study of the cost effectiveness of emergency obstetric trainings using both interviews and focus groups of participants from emergency obstetric training sessions determined that short workshops are a worthwhile investment because of significant knowledge uptake over a short period of training with little cost 18 . Equally as important, the study of 3‐ to 5‐day emergency obstetric and neonatal courses focusing on interactive learning sessions with short lectures, simulation training, role play workshops, and mentoring in sub‐Saharan Africa and Asia revealed improved knowledge and skills for levels of healthcare providers, including all cadres of providers giving maternity care, after the course 19 .…”
Section: Discussionsupporting
confidence: 57%
“…A review of 116 1‐ to 5‐day simulation‐based studies from around the world on emergency obstetric care training for hospital staff at all levels, demonstrated that similar to our course, short competency‐based training can result in a change in clinical practice and significant improvement in skills and knowledge 17 . Similarly, in Kenya, a study of the cost effectiveness of emergency obstetric trainings using both interviews and focus groups of participants from emergency obstetric training sessions determined that short workshops are a worthwhile investment because of significant knowledge uptake over a short period of training with little cost 18 . Equally as important, the study of 3‐ to 5‐day emergency obstetric and neonatal courses focusing on interactive learning sessions with short lectures, simulation training, role play workshops, and mentoring in sub‐Saharan Africa and Asia revealed improved knowledge and skills for levels of healthcare providers, including all cadres of providers giving maternity care, after the course 19 .…”
Section: Discussionsupporting
confidence: 57%
“…For specific interventions being implemented, training of varying length of days were generally reported as being effective for improving identification and decision making. Training such as these have been shown to be cost‐effective [40] and guarantee value for money across multiple stakeholders [41]. However, as our review shows these trainings need to be targeted at the right personnel who have been motivated and equipped sufficiently to be able to make the right decision on referral for the women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study may provide valuable information to guide decision-making associated with the HA management. Compared to traditional frameworks, the SROI incorporates a broader concept of value into the evaluation of healthcare interventions through engaging multiple stakeholders to account for all relevant perspectives, using financial proxies to account for complex outcomes which are difficult to monetize, and considering both positive and negative impacts [ 43 ]. Moreover, the chain of events going from the investment in specific activities to their impact can be easily followed for each stakeholder and proposal within the SROI framework [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional frameworks, the SROI incorporates a broader concept of value into the evaluation of healthcare interventions through engaging multiple stakeholders to account for all relevant perspectives, using financial proxies to account for complex outcomes which are difficult to monetize, and considering both positive and negative impacts [ 43 ]. Moreover, the chain of events going from the investment in specific activities to their impact can be easily followed for each stakeholder and proposal within the SROI framework [ 43 ]. Regarding stakeholders, patients and informal caregivers were included as stakeholders for both the identification and evaluation of proposals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation